2013
DOI: 10.1371/currents.dis.53e08b951d59ff913ab8b9bb51c4d0de
|View full text |Cite
|
Sign up to set email alerts
|

Non-Communicable Diseases in Emergencies: A Call to Action

Abstract: Recent years have demonstrated the devastating health consequences of complex emergencies and natural disasters and thereby highlighted the importance of comprehensive and collaborative approaches to humanitarian responses and risk reduction. Simultaneously, noncommunicable diseases are now recognised as a real and growing threat to population health and development; a threat that is magnified by and during emergencies. Noncommunicable diseases, however, continue to receive little attention from humanitarian o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 15 publications
0
76
0
1
Order By: Relevance
“…2 The findings of this review suggest that addressing chronic disease in disaster planning and response efforts may help mitigate cardiac morbidity and mortality following a disaster. Given the changing global burden of disease, planning for the monitoring and management of cardiac disease in the post-disaster period should be prioritized.…”
Section: Discussionmentioning
confidence: 95%
“…2 The findings of this review suggest that addressing chronic disease in disaster planning and response efforts may help mitigate cardiac morbidity and mortality following a disaster. Given the changing global burden of disease, planning for the monitoring and management of cardiac disease in the post-disaster period should be prioritized.…”
Section: Discussionmentioning
confidence: 95%
“…While a United Nations (UN) Political Declaration and a World Health Organization (WHO) Global Action Plan recognise the significant contribution of NCDs to global morbidity and mortality [1, 2], the problem of NCDs during emergencies and in humanitarian response has been underrecognised [3]. The evidence base is negligible: a systematic review on the effectiveness of interventions for NCDs in humanitarian settings found just eight studies published over the last 35 years, four of which came from the same refugee camp in Jordan [4].…”
mentioning
confidence: 99%
“…We welcome Tonelli et al 's1 contribution to raising the profile of non-communicable diseases (NCD), especially on NCD medicines in humanitarian emergencies, a topic that to date has received very little attention 2. However, we would question the message and conclusion of this paper on three grounds.…”
mentioning
confidence: 91%